Physiological, perceptual, and technical responses to on-court tennis training on hard and clay courts - Reid, M. M.; Duffield, R.; Minett, G. M.; Sibte, N.; Murphy, A. P.; Baker, J. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to investigate the effect of court surface (clay vs. hard court) on technical, physiological, and perceptual responses to on-court tennis training. Four high-performance junior male players performed 2 identical training sessions on hard and clay courts, respectively. Sessions included both physical conditioning and technical elements as led by the coach. Each session was filmed for later notational analysis of stroke count and error rates. Furthermore, players wore a global positioning satellite device to measure distance covered during each session, while heart rate, countermovement jump distance, and capillary blood measures of metabolites were measured before, during, and after each session. Additionally, a respective coach and athlete rating of perceived exertion (RPE) were measured after each session. Total duration and distance covered during each session were comparable (p > 0.05; d < 0.20). Although forehand and backhands stroke volume did not differ between sessions (p > 0.05; d < 0.30), large effects for increased unforced and forced errors were present on the hard court (p > 0.05; d > 0.90). Furthermore, large effects for increased heart rate, blood lactate, and RPE values were evident on clay compared with hard courts (p > 0.05; d > 0.90). Additionally, although player and coach RPE on hard courts were similar, there were large effects for coaches to underrate the RPE of players on clay courts (p > 0.05; d > 0.90). In conclusion, training on clay courts results in trends for increased heart rate, lactate, and RPE values, suggesting that sessions on clay courts tend towards higher physiological and perceptual loads than hard courts. Furthermore, coaches seem effective at rating player RPE on hard courts but may underrate the perceived exertion of sessions on clay courts.